On the exact position of the tribe Incolacridini in the modern classification of grasshoppers (Orthoptera: Acrididae) - Storozhenko, Sergey Yu. (Zootaxa, 2021)
Incolacridinae is considered as a separate subfamily, not as a tribe of subfamily Catantopinae. It consists of four genera: Incolacris C. Willemse, 1932, stat. resurr., Stolzia C. Willemse, 1930, Bettotania C. Willemse, 1933, and Asymmetritania gen. nov. (type species: Stolzia vietnamensis Storozhenko, 2020). New combinations are proposed: Incolacris jianfengensis (Zheng et Ma, 1989), comb. nov., Asymmetritania asymmetrica (Ingrisch, 1989), comb. nov., and A. vietnamensis (Storozhenko, 2020), comb. nov. The diagnosis of subfamily and genera, a key to genera and an annotated list of the species of Incolacridinae are also given.